ANALISIS PERBAIKAN PROSES PRODUKSI PADA PT SUMBER TEKNIK SENTOSA - Damar Suryo Bowo (Universitas muhammadiyah malang, 2018)
This study aimed to analyze the production process of Dies Forging Piston Wheel Cylinder and to suggest the improvement for the production. The data were analyzed by Time-Function Mapping, Cause and Effect, and Failure Mode and Effect Analysis (FMEA). The findings showed that there were seven production phases of Dies Forging Piston Wheel Cylinder. After figuring out the troubled phase, the next step was searching for the cause and the solution of the problem using FMEA. The FMEA calculation indicated 4 problems i.e. the employees working on another product, vibrating clamp machines, employees producing jig, and unavailability of jig. The main problem was detected based on the highest score of Risk Priority Number (RPN) that calculation indicator was severity, occurrence, and detection.